Film and laminate
Patent Information
- Application Number
- CN202180076869.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-11-19
- Filing Date
- 2021-11-24
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2041-11-24
AI Technical Summary
In the prior art, the metal wiring is prone to deformation when the film is bonded to it, and the adhesion of the existing laminated film is insufficient.
The film uses a dielectric loss tangent of less than 0.005, and the surface elastic modulus at 160℃ and 300℃ is less than the internal modulus. It also contains polymers such as liquid crystal polymers and fluoropolymers. The peel strength of the copper layer used in the laminate is above 0.5kN/m.
It effectively inhibits the deformation of metal wiring under high temperature conditions, and improves the adhesion strength and stability between the film and the metal layer.
Smart Images

Figure BDA0004228382520000171 
Figure BDA0004228382520000181 
Figure BDA0004228382520000361
Abstract
Description
Technical Field
[0001] This invention relates to a membrane and a laminate. Background Technology
[0002] In recent years, the frequencies used in communication equipment have tended to become very high. In order to suppress transmission losses in high-frequency bands, it is necessary to reduce the relative permittivity and dielectric loss tangent of the insulating materials used in circuit boards.
[0003] Polyimide has been widely used as an insulating material for circuit boards in the past, but liquid crystal polymers with high heat resistance, low water absorption and low loss in the high frequency band have attracted attention.
[0004] As a conventional liquid crystal polymer film, for example, Patent Document 1 describes a liquid crystal polyester film, which at least comprises a liquid crystal polyester. When the first orientation degree is set as the orientation degree relative to a first direction parallel to the main surface of the liquid crystal polyester film, and the second orientation degree is set as the orientation degree relative to a second direction parallel to the main surface and orthogonal to the first direction, the ratio of the first orientation degree to the second orientation degree, i.e., the first orientation degree / second orientation degree, is 0.95 or more and 1.04 or less, and the third orientation degree of the liquid crystal polyester, measured by wide-angle X-ray scattering in the direction parallel to the main surface, is 60.0% or more.
[0005] Furthermore, as a conventional laminated film, for example, Patent Document 2 describes a method for manufacturing a peelable laminated film, characterized in that the peelable laminated film includes an A layer containing a cellulose ester and a B layer containing a resin that is different from the cellulose ester and capable of solution film formation, the adhesion between the A layer and the B layer is 5 N / cm or less, wherein a dopant A for forming the A layer containing at least the cellulose ester and a solvent, and a dopant B for forming the B layer containing at least a resin that is different from the cellulose ester and a solvent are simultaneously or sequentially cast onto a casting support and laminated, and then the laminate of the dopant A and the dopant B is peeled off from the casting support and dried.
[0006] Previous technical documents
[0007] Patent documents
[0008] Patent Document 1: Japanese Patent Application Publication No. 2020-26474
[0009] Patent Document 2: Japanese Patent Application Publication No. 2013-46992 Summary of the Invention
[0010] The technical problem to be solved by the invention
[0011] One embodiment of the present invention aims to provide a film that can suppress deformation of metal wiring when bonded to it.
[0012] Furthermore, another embodiment of the present invention aims to provide a laminate that uses the above-described film.
[0013] means for solving technical problems
[0014] The methods used to solve the above problems include the following approaches.
[0015] <1> A film having a dielectric loss tangent of less than 0.005, wherein at least one surface has an elastic modulus at 160°C that is less than that of the interior at 160°C.
[0016] <2> according to <1> The membrane wherein the loss tangent of the surface at 160°C is greater than or equal to 0.03.
[0017] <3> according to <1> or <2> The membrane, wherein the elastic modulus of the interior at 160°C is 0.5 GPa or higher.
[0018] <4> A film having a dielectric loss tangent of less than 0.005, wherein at least one surface has an elastic modulus at 300°C that is less than that of the interior at 300°C.
[0019] <5> according to <4> The membrane, wherein the loss tangent of the surface at 300°C is 0.1 or higher.
[0020] <6> according to <4> or <5> The membrane, wherein the elastic modulus of the interior at 300°C is 0.1 GPa or higher.
[0021] <7> according to <1> to <6> The membrane described in any one of the following examples has a coefficient of linear expansion of -20ppm / K to 50ppm / K.
[0022] <8> according to <1> to <7> The membrane described in any one of the following statements comprises a filler.
[0023] <9> according to <8> The membrane wherein the number density of the filler inside is greater than the number density on the surface.
[0024] <10> according to <1> to <9> The membrane described in any one of the following methods comprises at least one polymer selected from liquid crystal polymers, fluorinated polymers, polymers of compounds having cyclic aliphatic hydrocarbon groups and groups having olefinic unsaturated bonds, polyphenylene ethers, and aromatic polyether ketones.
[0025] <11> according to <10> The film, wherein the liquid crystal polymer has a structural unit represented by any of formulas (1) to (3).
[0026] Formula (1)-O-Ar 1 -CO-
[0027] Formula (2)-CO-Ar 2 -CO-
[0028] Formula (3)-X-Ar 3 -Y-
[0029] In equations (1) to (3), Ar 1 Ar represents phenylene, naphthylene, or biphenylene. 2 and Ar 3 Each of these groups independently represents a phenylene, naphthylene, biphenylene, or a group represented by formula (4) below, where X and Y independently represent an oxygen atom or an imino atom, respectively. 1 ~Ar 3 The hydrogen atoms in the atom can be independently replaced by halogen atoms, alkyl groups, or aryl groups.
[0030] Formula (4)-Ar 4 -Z-Ar 5 -
[0031] In equation (4), Ar 4 and Ar 5 Each can be represented independently as either phenylene or naphthylene, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkylene group.
[0032] <12> A film having a dielectric loss tangent of less than 0.010, wherein at least one surface has an elastic modulus at 160°C that is less than that of the interior at 160°C.
[0033] <13> A film having a dielectric loss tangent of less than 0.010, wherein at least one surface has an elastic modulus at 300°C that is less than that of the interior at 300°C.
[0034] <14> according to <1> to <3> and <7> to <12> The membrane described in any one of the following statements has a layer A and a layer B disposed on at least one side of the layer A, wherein the elastic modulus of the surface of the layer B at 160°C is less than the elastic modulus of the interior at 160°C.
[0035] <15> according to <4> to <11> or <13> The membrane according to any one of the following methods has a layer A and a layer B disposed on at least one side of the layer A, wherein the elastic modulus of the surface of the layer B at 300°C is less than the elastic modulus of the interior at 300°C.
[0036] <16> according to <14> or <15> The membrane further comprises layer C, wherein the membrane sequentially comprises layer B, layer A and layer C.
[0037] <17> A laminated body having: <14> or <15> The membrane; and the metal layer disposed on the surface of the membrane on the side of layer A.
[0038] <18> A laminated body having: <14> to <16> The membrane as described in any one of the above statements; and the metal layer disposed on the surface of the membrane on the side of layer B.
[0039] <19> A laminated body having: <16> The membrane; a metal layer disposed on the surface of the membrane on the side of layer B; and a metal layer disposed on the surface of the membrane on the side of layer C.
[0040] <20> according to <18> or <19> In the aforementioned laminate, the metal layer disposed on the side of layer B is a copper layer disposed on the surface of layer B, and the peel strength between layer B and the copper layer is 0.5 kN / m or more.
[0041] <21> according to <19> In the aforementioned laminate, the metal layer disposed on the side of layer C is a copper layer disposed on the surface of layer C, and the peel strength between layer C and the copper layer disposed on the side of layer C is 0.5 kN / m or more.
[0042] <22> according to <17> to <21> The laminate as described in any one of the following statements, wherein the thickness of layer B is greater than the thickness of the metal layer.
[0043] Invention Effects
[0044] According to one embodiment of the present invention, a film capable of suppressing deformation of metal wiring can be provided when bonded to metal wiring.
[0045] Furthermore, according to another embodiment of the present invention, it is possible to provide a laminate using the above-described film. Detailed Implementation
[0046] The present invention will now be described in detail. The description of the constituent elements described below can be performed according to a representative embodiment of the present invention, but the present invention is not limited to this embodiment.
[0047] In addition, in this specification, the "~" sign indicating a numerical range is used to mean that the numerical values recorded before and after it are included as lower and upper limits.
[0048] In the numerical ranges described in stages in this invention, the upper or lower limit value described in one numerical range can be replaced by the upper or lower limit value of other numerical ranges described in stages. Furthermore, in the numerical ranges described in this invention, the upper or lower limit value of that numerical range can be replaced by the values shown in the embodiments.
[0049] Furthermore, in the designation of groups (atomic groups) in this specification, the designations without indicating whether they are substituted or unsubstituted include both unsubstituted and substituted groups. For example, "alkyl" means that it includes not only unsubstituted alkyl groups (unsubstituted alkyl groups) but also substituted alkyl groups (substituted alkyl groups).
[0050] In this specification, "(meth)acrylic acid" is a term used to encompass both acrylic acid and methacrylic acid, and "(meth)acryloyl" is a term used to encompass both acryloyl and methacryloyl.
[0051] Furthermore, the term "process" in this specification is not only used for independent processes, but also includes processes that achieve their intended purpose, even if they cannot be clearly distinguished from other processes.
[0052] Furthermore, in this invention, "mass%" and "weight%" are synonyms, and "parts of mass" and "parts of weight" are synonyms.
[0053] Furthermore, in this invention, a combination of two or more preferred methods is a more preferred method.
[0054] Furthermore, unless otherwise specified, the weight-average molecular weight (Mw) and number-average molecular weight (Mn) in this invention are calculated by using a gel permeation chromatography (GPC) analysis apparatus with a TSKgel SuperHM-H column (trade name manufactured by Tosoh Corporation), with PFP (pentafluorophenol) / chloroform = 1 / 2 (mass ratio) as solvent, using a differential refractometer, and using polystyrene as a standard substance.
[0055] (membrane)
[0056] In the first embodiment of the membrane involved in the present invention, the dielectric loss tangent is less than 0.005, and the elastic modulus of at least one surface at 160°C is less than the elastic modulus of the interior at 160°C.
[0057] Furthermore, in the second embodiment of the membrane according to the present invention, the dielectric loss tangent is 0.005 or less, and the elastic modulus of at least one surface at 300°C is less than that of the interior at 300°C.
[0058] Furthermore, in the third embodiment of the membrane according to the present invention, the dielectric loss tangent is 0.010 or less, and the elastic modulus of at least one surface at 160°C is less than that of the interior at 160°C.
[0059] Furthermore, in the fourth embodiment of the membrane according to the present invention, the dielectric loss tangent is 0.010 or less, and the elastic modulus of at least one surface at 300°C is less than that of the interior at 300°C.
[0060] Here, the surface of the polymer film refers to the outer surface of the polymer film (the surface in contact with air or the substrate). In this invention, the "surface" of the film refers to the region from the outermost surface of the film to a position equivalent to 10% of the film thickness when the film thickness is 30 μm or less. When the film thickness exceeds 30 μm, the "surface" refers to the region from the outermost surface of the film to a position 3 μm away along the thickness direction.
[0061] In this invention, the "interior" of the membrane refers to the region extending from the center of the membrane in the thickness direction to a position equivalent to ±5% of the membrane thickness when the membrane thickness is 30 μm or less. When the membrane thickness exceeds 30 μm, the "interior" refers to the region extending from the center of the membrane in the thickness direction to a position ±1.5 μm away along the thickness direction.
[0062] In addition, unless otherwise specified, the first embodiment and the second embodiment described above will be referred to as "the membrane involved in the present invention" or "membrane" in this specification.
[0063] Regarding conventional films, such as the one described in Patent Document 1, there are many films with a large coefficient of linear expansion. In the film described in Patent Document 1, it is known that deformation of the metal wiring occurs when it is bonded to the metal wiring.
[0064] The inventors have conducted in-depth research and discovered that by adopting the above structure, it is possible to provide a film that can suppress the deformation of metal wiring when it is bonded to metal wiring.
[0065] The detailed mechanism by which the above effects are achieved is not yet clear, but it is speculated to be as follows.
[0066] In the membrane according to the present invention, at least one surface has a lower elastic modulus at 160°C than the interior surface at 160°C, thus allowing the membrane to deform according to the shape of the metal wiring when bonded to it. Furthermore, in the membrane according to the present invention, at least one surface has a lower elastic modulus at 300°C than the interior surface at 300°C, thus allowing the membrane to deform according to the shape of the metal wiring when bonded to it. As a result, deformation of the metal wiring can be suppressed.
[0067] From the viewpoint of suppressing deformation of metal wiring when bonding with metal wiring, the dielectric loss tangent of the film involved in the present invention is 0.010 or less, preferably 0.005 or less, and more preferably more than 0 and 0.003 or less.
[0068] The dielectric loss tangent in this invention is measured by the following method.
[0069] The dielectric loss tangent was measured at a frequency of 10 GHz using the resonant perturbation method. A 10 GHz cavity resonator (KANTO Electronic Application and Development Inc. CP531) was connected to a network analyzer (E8363B, manufactured by Agilent Technology). A sample (width: 2.0 mm × length: 80 mm) was inserted into the cavity resonator. The dielectric loss tangent was measured based on the change in resonant frequency before and after insertion over a period of 96 hours at 25°C and 60% RH.
[0070] When measuring each layer, unnecessary layers can be removed using a razor or similar tool to prepare an evaluation sample containing only the target layer. Furthermore, due to the thinness of the layers, if it is difficult to remove a single film, the layers measured using a razor or similar tool can be removed, and the resulting powdered sample can be used.
[0071] In a first embodiment of the membrane involved in the present invention, at least one surface has an elastic modulus at 160°C that is less than that of the interior at 160°C.
[0072] Furthermore, in the second embodiment of the membrane according to the present invention, at least one surface has an elastic modulus at 300°C that is less than that of the interior at 300°C.
[0073] The membrane involved in this invention preferably has at least one surface with an elastic modulus at 160°C that is less than the interior elastic modulus at 160°C, and at least one surface with an elastic modulus at 300°C that is less than the interior elastic modulus at 300°C.
[0074] The difference between the elastic modulus of at least one surface at 160°C and the elastic modulus of the interior at 160°C is preferably 0.1 GPa or more, more preferably 0.8 GPa or more, and even more preferably 1.5 GPa or more. The upper limit of the above difference is not particularly limited, for example, it is 3.0 GPa.
[0075] The difference between the elastic modulus of at least one surface at 300°C and the elastic modulus of the interior at 300°C is preferably 0.1 GPa or more, more preferably 0.5 GPa or more, and even more preferably 0.8 GPa or more. The upper limit of the above difference is not particularly limited, for example, it is 2.0 GPa.
[0076] The loss tangent of at least one surface of the membrane involved in this invention is preferably 0.03 or more, more preferably 0.1 or more, and even more preferably 0.2 or more. The upper limit of the loss tangent of the surface at 160°C is not particularly limited, for example, it is 1.0.
[0077] Furthermore, the loss tangent of at least one surface of the membrane according to the present invention is preferably 0.1 or more, more preferably 0.3 or more, and even more preferably 1.0 or more. The upper limit of the loss tangent of the surface at 300°C is not particularly limited, for example, it is 10.
[0078] The elastic modulus of the membrane involved in this invention at 160°C is preferably 0.5 GPa or more, more preferably 1.0 GPa or more, even more preferably 1.5 GPa or more, and particularly preferably 2.0 GPa or more. The upper limit of the elastic modulus at 160°C is not particularly limited, for example, it is 3.0 GPa.
[0079] Furthermore, the elastic modulus of the membrane involved in this invention at 300°C is preferably 0.1 GPa or more, more preferably 0.5 GPa or more, even more preferably 0.7 GPa or more, and particularly preferably 1.0 GPa or more. The upper limit of the elastic modulus of the membrane at 300°C is not particularly limited, for example, it is 2.0 GPa.
[0080] The elastic modulus of at least one surface of the membrane involved in this invention at 160°C is preferably 3.0 GPa or less, more preferably 1.0 GPa or less, and even more preferably 0.7 GPa or less. The lower limit of the elastic modulus of the surface at 160°C is not particularly limited, for example, it is 0.01 GPa.
[0081] Furthermore, the elastic modulus of at least one surface of the membrane involved in this invention at 300°C is preferably 2.0 GPa or less, more preferably 0.7 GPa or less, and even more preferably 0.3 GPa or less. The lower limit of the elastic modulus of the surface at 300°C is not particularly limited, for example, it is 0.001 GPa.
[0082] The elastic modulus of the film involved in this invention is within the above-mentioned range at various temperatures. Therefore, when bonded to metal wiring, the film can deform according to the shape of the metal wiring, thus suppressing metal wiring deformation. Consequently, the temperatures with the above-mentioned elastic modulus can be used as indicators of the processing temperature in the manufacturing process when bonding the film involved in this invention to metal (e.g., metal foil and metal wiring).
[0083] From the viewpoint of suppressing deformation of metal wiring, the elastic modulus of the side in contact with the metal layer is preferably within the above range.
[0084] The elastic modulus and loss tangent in this invention are measured by the following methods.
[0085] A sample for cross-sectional evaluation was prepared by cutting a film coated with UV (ultraviolet-curable) resin using a slicer. Then, the sample was observed using a scanning probe microscope (SPA400, manufactured by Seiko Instruments Inc.) in VE-AFM mode to calculate the surface and internal storage modulus and the loss tangent (loss modulus / storage modulus).
[0086] In addition, the elastic modulus in this invention refers to the "energy storage modulus".
[0087] The elastic modulus at 160℃ refers to the elastic modulus measured when the sample temperature is adjusted to 160℃.
[0088] The elastic modulus at 300℃ refers to the elastic modulus measured when the sample temperature is adjusted to 300℃.
[0089] The linear expansion coefficient of the membrane involved in this invention is preferably -20ppm / K to 50ppm / K. From the viewpoint of suppressing deformation of metal wiring when bonding with metal wiring, it is more preferably -10ppm / K to 40ppm / K, even more preferably 0ppm / K to 35ppm / K, particularly preferably 10ppm / K to 30ppm / K, and even more preferably 15ppm / K to 25ppm / K.
[0090] The coefficient of linear expansion in this invention is measured by the following method.
[0091] Using a thermomechanical analysis (TMA) apparatus, a tensile load of 1g was applied to both ends of a membrane with a width of 5mm and a length of 20mm, and the temperature was increased to 25℃ to 200℃ at a rate of 5℃ / min. Then, the membrane was cooled to 30℃ at a rate of 20℃ / min, and then heated again at a rate of 5℃ / min. The coefficient of linear expansion was calculated based on the slope of the TMA curve between 30℃ and 150℃ at this point.
[0092] Furthermore, when it is difficult to measure the coefficient of linear expansion using the methods described above, the following method can be used for measurement.
[0093] The membrane was sectioned using a microtome and an optical microscope equipped with a heating stage system (HS82, manufactured by Mettler-Toledo International Inc.) was installed. The temperature was then increased to 25°C–200°C at a rate of 5°C / min. Afterward, it was cooled to 30°C at a rate of 20°C / min, and then increased again at a rate of 5°C / min. The membrane thickness (ts30) at 30°C and the membrane thickness (ts150) at 150°C were evaluated. The value obtained by dividing the dimensional change by the temperature change ((ts150-ts30) / (150-30)) was calculated and used as the coefficient of linear expansion of the membrane.
[0094] The film involved in this invention preferably comprises a polymer with a dielectric loss tangent of 0.01 or less. The dielectric loss tangent of the polymer is, for example, 0.010 or less, preferably 0.008 or less, more preferably 0.0075 or less, further preferably 0.006 or less, and especially preferably 0.005 or less. Furthermore, from the viewpoint of the dielectric loss tangent of the polymer film and its adhesion to a metal (e.g., a metal layer), the dielectric loss tangent of the polymer is preferably 0.004 or less, more preferably 0.0035 or less, and especially preferably 0.003 or less. The lower limit value of the dielectric loss tangent of the polymer is not particularly limited, for example, it may exceed 0.
[0095] The dielectric loss tangent of the polymer in this invention is determined or isolated by using a sample of the polymer that has been made into a powder, and the measurement is performed according to the above-described method for measuring the dielectric loss tangent.
[0096] Examples of polymers with a dielectric loss tangent of 0.005 or less include liquid crystal polymers, fluorinated polymers, polymers of compounds having cyclic aliphatic hydrocarbon groups and olefinic unsaturated bonds, polyetheretherketone, polyolefins, polyamides, polyesters, polyphenylene sulfide, polyetherketone, polycarbonate, polyethersulfone, polyphenylene ether and its modified forms, and thermoplastic resins such as polyetherimide; elastomers such as copolymers of glycidyl methacrylate and polyethylene; and thermosetting resins such as phenolic resins, epoxy resins, polyimide resins, and cyanate ester resins.
[0097] From the viewpoint of further reducing the dielectric loss tangent of the film, the polymer is preferably selected from at least one polymer selected from liquid crystal polymers, fluorinated polymers, polymers having cyclic aliphatic hydrocarbon groups and groups having olefinic unsaturated bonds, polyphenylene ether, and aromatic polyether ketones, and more preferably at least one polymer selected from liquid crystal polymers and fluorinated polymers. From the viewpoint of film-forming properties and mechanical strength, the polymer is preferably a liquid crystal polymer, and from the viewpoint of dielectric loss tangent, it is preferably a fluorinated polymer.
[0098] -Liquid Crystal Polymer-
[0099] In this invention, the type of liquid crystal polymer is not particularly limited, and known liquid crystal polymers can be used.
[0100] Furthermore, the liquid crystal polymer can be a thermotropic liquid crystal polymer that exhibits liquid crystal properties in the molten state, or a lyotropic liquid crystal polymer that exhibits liquid crystal properties in the solution state. Moreover, when the liquid crystal polymer is a thermotropic liquid crystal polymer, it is preferably a liquid crystal polymer that melts at a temperature of 450°C or below.
[0101] Examples of liquid crystal polymers include liquid crystal polyesters, liquid crystal polyester amides in which amide bonds are introduced into liquid crystal polyesters, liquid crystal polyester ethers in which ether bonds are introduced into liquid crystal polyesters, and liquid crystal polyester carbonates in which carbonate bonds are introduced into liquid crystal polyesters.
[0102] Furthermore, from the viewpoint of liquid crystal properties, the liquid crystal polymer is preferably a polymer having an aromatic ring, and more preferably an aromatic polyester or an aromatic polyesteramide.
[0103] Furthermore, liquid crystal polymers can be polymers in which bonds derived from isocyanates, such as imide bonds, carbodiimide bonds, and isocyanate bonds, are further introduced into aromatic polyesters or aromatic polyesteramides.
[0104] Furthermore, the liquid crystal polymer is preferably a fully aromatic liquid crystal polymer made using only aromatic compounds as raw material monomers.
[0105] Examples of liquid crystal polymers include the following.
[0106] 1) A liquid crystal polymer formed by condensation of (i) an aromatic hydroxycarboxylic acid, (ii) an aromatic dicarboxylic acid, and (iii) at least one compound selected from aromatic diols, aromatic hydroxyamines, and aromatic diamines.
[0107] 2) Liquid crystal polymers formed by the condensation polymerization of various aromatic hydroxycarboxylic acids.
[0108] 3) A liquid crystal polymer formed by condensation of (i) an aromatic dicarboxylic acid and (ii) at least one compound selected from aromatic diols, aromatic hydroxylamines and aromatic diamines.
[0109] 4) A liquid crystal polymer formed by condensation polymerization of (i) polyesters such as polyethylene terephthalate and (ii) aromatic hydroxycarboxylic acids.
[0110] Here, aromatic hydroxycarboxylic acids, aromatic dicarboxylic acids, aromatic diols, aromatic hydroxyamines, and aromatic diamines can also be independently substituted with polycondensable derivatives.
[0111] For example, by converting the carboxyl group to an alkoxycarbonyl group or an aryloxycarbonyl group, aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids can be replaced with aromatic hydroxycarboxylic acid esters and aromatic dicarboxylic acid esters.
[0112] By converting the carboxyl group to a haloformyl group, aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids can be replaced with aromatic hydroxycarboxylic acid halides and aromatic dicarboxylic acid halides.
[0113] By converting the carboxyl group to an acyloxycarbonyl group, aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids can be replaced with aromatic hydroxycarboxylic anhydrides and aromatic dicarboxylic anhydrides.
[0114] Examples of polymerizable derivatives of compounds containing hydroxyl groups, such as aromatic hydroxycarboxylic acids, aromatic diols, and aromatic hydroxyamines, include derivatives (acylated products) formed by acylation of hydroxyl groups to acyloxy groups.
[0115] For example, by acylation of the hydroxyl group to an acyloxy group, aromatic hydroxycarboxylic acids, aromatic diols, and aromatic hydroxylamines can be replaced with acylated products.
[0116] Examples of polymerizable derivatives of compounds containing amino groups, such as aromatic hydroxylamines and aromatic diamines, include derivatives (acylated products) formed by acylation of amino groups to amide groups.
[0117] For example, by acylation of amino groups to amide groups, aromatic hydroxylamines and aromatic diamines can be replaced with acylated products.
[0118] From the viewpoint of liquid crystal properties, the liquid crystal polymer preferably has structural units represented by any of the following formulas (1) to (3), more preferably has structural repeating units represented by the following formula (1), and especially preferably has structural units represented by the following formula (1), structural units represented by the following formula (2), and structural units represented by the following formula (3). Hereinafter, the structural units represented by formula (1) and the like will also be referred to as "unit (1)" and the like.
[0119] Formula (1)-O-Ar 1 -CO-
[0120] Formula (2)-CO-Ar 2-CO-
[0121] Formula (3)-X-Ar 3 -Y-
[0122] In equations (1) to (3), Ar 1 Ar represents phenylene, naphthylene, or biphenylene. 2 and Ar 3 Each of these groups independently represents a phenylene, naphthylene, biphenylene, or a group represented by formula (4) below, where X and Y independently represent an oxygen atom or an imino atom, respectively. 1 ~Ar 3 The hydrogen atoms in the atom can be independently replaced by halogen atoms, alkyl groups, or aryl groups.
[0123] Formula (4)-Ar 4 -Z-Ar 5 -
[0124] In equation (4), Ar 4 and Ar 5 Each can be represented independently as either phenylene or naphthylene, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkylene group.
[0125] Examples of halogen atoms include fluorine, chlorine, bromine, and iodine.
[0126] Examples of the aforementioned alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-hexyl, 2-ethylhexyl, n-octyl, and n-decyl. The preferred number of carbon atoms in the alkyl group is 1 to 10.
[0127] Examples of the aforementioned aryl groups include phenyl, o-tolyl, m-tolyl, p-tolyl, 1-naphthyl, and 2-naphthyl. The preferred number of carbon atoms in the aryl group is 6 to 20.
[0128] Ar 1 ~Ar 3 When the hydrogen atom is replaced by a halogen atom, alkyl group or aryl group, the number of substituents is preferably 2 or less, more preferably 1.
[0129] Examples of the aforementioned alkylene groups include methylene, 1,1-ethanediyl, 1-methyl-1,1-ethanediyl, 1,1-butanediyl, and 2-ethyl-1,1-hexanediyl. The alkylene group preferably has 1 to 10 carbon atoms.
[0130] Unit (1) is a structural unit derived from aromatic hydroxycarboxylic acids.
[0131] As unit (1), Ar is preferred. 1This is the phenylene approach (derived from the structural unit of p-hydroxybenzoic acid), and Ar 1 It is either 2,6-naphthyl (derived from the structural unit of 6-hydroxy-2-naphthoic acid) or 4,4'-biphenyl (derived from the structural unit of 4'-hydroxy-4-biphenylcarboxylic acid).
[0132] Unit (2) is a structural unit derived from aromatic dicarboxylic acids.
[0133] As unit (2), Ar is preferred. 2 p-phenylene (derived from the structural unit of terephthalic acid), Ar 2 It is a m-phenylene-based (derived from the structural unit of isophthalic acid), Ar 2 It is in the 2,6-naphthyl form (derived from the structural unit of 2,6-naphthoic acid), or Ar 2 It is in the form of diphenyl ether-4,4'-diyl (derived from the structural unit of diphenyl ether-4,4'-dicarboxylic acid).
[0134] Unit (3) is a structural unit derived from aromatic diols, aromatic hydroxylamines or aromatic diamines.
[0135] As unit (3), Ar is preferred. 3 Ar3 is in the form of a phenylene group (derived from the structural unit of hydroquinone, p-aminophenol, or p-phenylenediamine), Ar3 is in the form of a m-phenylene group (derived from the structural unit of isophthalic acid), or Ar... 3 It is in the form of 4,4'-biphenyl (derived from the structural unit of 4,4'-dihydroxybiphenyl, 4-amino-4'-hydroxybiphenyl or 4,4'-diaminobiphenyl).
[0136] The content of unit (1) relative to the total amount of all structural units is preferably 30 mol% or more, more preferably 30 mol% to 80 mol%, even more preferably 30 mol% to 60 mol%, and especially preferably 30 mol% to 40 mol%.
[0137] The content of unit (2) relative to the total amount of all structural units is preferably 35 mol% or less, more preferably 10 mol% to 35 mol%, even more preferably 20 mol% to 35 mol%, and especially preferably 30 mol% to 35 mol%.
[0138] The content of unit (3) relative to the total amount of all structural units is preferably 35 mol% or less, more preferably 10 mol% to 35 mol%, even more preferably 20 mol% to 35 mol%, and especially preferably 30 mol% to 35 mol%.
[0139] The higher the content of unit (1), the easier it is to improve heat resistance, strength and rigidity, but if there is too much, the solubility in solvents will be reduced.
[0140] Furthermore, the total amount of all structural units is the sum of the molar amounts of each structural unit. The molar amount of each structural unit is calculated by dividing the mass of each structural unit constituting the liquid crystal polymer by the formula weight of each structural unit.
[0141] When the ratio of the content of unit (2) to the content of unit (3) is expressed as [content of unit (2)] / [content of unit (3)] (moles / moles), it is preferably 0.9 / 1 to 1 / 0.9, more preferably 0.95 / 1 to 1 / 0.95, and even more preferably 0.98 / 1 to 1 / 0.98.
[0142] Furthermore, the liquid crystal polymer may have two or more units (1) to (3) independently. Also, the liquid crystal polymer may have other structural units besides units (1) to (3). The content of other structural units relative to the total amount of all structural units is preferably 10 mol% or less, more preferably 5 mol% or less.
[0143] Liquid crystal polymers have excellent solubility in solvents, and therefore preferably have at least one imino unit (3) of X and Y, that is, at least one of the structural units derived from aromatic hydroxylamine and the structural unit derived from aromatic diamine, and more preferably have only one imino unit (3) of X and Y.
[0144] Liquid crystal polymers are preferably manufactured by melt polymerization of raw material monomers corresponding to the structural units constituting the liquid crystal polymer. Melt polymerization can also be carried out in the presence of a catalyst. Examples of catalysts include metal compounds such as magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, potassium acetate, and antimony trioxide; and nitrogen-containing heterocyclic compounds such as 4-(dimethylamino)pyridine and 1-methylimidazole. Nitrogen-containing heterocyclic compounds are preferred as catalysts. Furthermore, if necessary, melt polymerization can be further performed by solid-state polymerization.
[0145] The flow initiation temperature of the liquid crystal polymer is preferably 180°C or higher, more preferably 200°C or higher, and even more preferably 250°C or higher. Furthermore, the flow initiation temperature is preferably 350°C or lower, more preferably 330°C or lower, and even more preferably 310°C or lower. If the flow initiation temperature of the liquid crystal polymer is within the above range, it exhibits excellent solubility, heat resistance, strength, and rigidity, and the viscosity of the solution is suitable.
[0146] The flow onset temperature is also known as the flow temperature or viscous flow temperature, which is the temperature at which the flow begins when a capillary thermometer is used at 9.8 MPa (100 kg / cm²). 2The liquid crystal polymer was melted by heating at a rate of 4°C / min under a load, and when extruded from a nozzle with an inner diameter of 1 mm and a length of 10 mm, the temperature at which it exhibited a viscosity of 4,800 Pa·s (48,000 poise) became the benchmark for the molecular weight of the liquid crystal polymer (Naoyuki Koide, “Liquid Crystal Polymers - Synthesis / Molding / Application-”, CMCCo., Ltd., June 5, 1987, see p. 95).
[0147] Furthermore, the weight-average molecular weight of the liquid crystal polymer is preferably 1,000,000 or less, more preferably 3,000 to 300,000, even more preferably 5,000 to 100,000, and particularly preferably 5,000 to 30,000. If the weight-average molecular weight of the liquid crystal polymer is within the above range, the film after heat treatment exhibits excellent thermal conductivity, heat resistance, strength, and rigidity in the thickness direction.
[0148] -Fluoropolymers-
[0149] In this invention, the type of fluorinated polymer is not particularly limited, and known fluorinated polymers can be used.
[0150] Furthermore, examples of fluorinated polymers include fluorinated α-olefin monomers, i.e., homopolymers and copolymers comprising structural units derived from α-olefin monomers containing at least one fluorine atom. Also, examples of fluorinated polymers include copolymers comprising structural units derived from fluorinated α-olefin monomers and structural units derived from non-fluorinated olefin unsaturated monomers reactive to fluorinated α-olefin monomers.
[0151] Examples of fluorinated α-olefin monomers include CF2=CF2, CHF=CF2, CH2=CF2, CHCl=CHF, CClF=CF2, CCl2=CF2, CClF=CClF, CHF=CCl2, CH2=CClF, CCl2=CClF, CF3CF=CF2, CF3CF=CHF, CF3CH=CF2, CF3CH=CH2, CHF2CH=CHF, CF3CF=CF2, and perfluoro(alkyl) vinyl ethers (e.g., perfluoromethyl vinyl ether, perfluoropropyl vinyl ether, and perfluorooctyl vinyl ether). Preferably, the fluorinated α-olefin monomer is selected from at least one monomer chosen from tetrafluoroethylene (CF2=CF2), trifluorochloroethylene (CClF=CF2), (perfluorobutyl)ethylene, vinylidene fluoride (CH2=CF2), and hexafluoropropylene (CF2=CFCF3).
[0152] Examples of nonfluorinated olefinic unsaturated monomers include ethylene, propylene, butene, and olefinic unsaturated aromatic monomers (e.g., styrene and α-methylstyrene).
[0153] Fluorinated α-olefin monomers can be used alone or in combination with two or more monomers.
[0154] Furthermore, nonfluorinated olefin unsaturated monomers can be used alone or in combination with two or more.
[0155] Examples of fluorinated polymers include polychlorotrifluoroethylene (PCTFE), poly(chlorotrifluoroethylene-propylene), poly(ethylene-tetrafluoroethylene) (ETFE), poly(ethylene-chlorotrifluoroethylene) (ECTFE), poly(hexafluoropropylene), poly(tetrafluoroethylene) (PTFE), poly(tetrafluoroethylene-ethylene-propylene), poly(tetrafluoroethylene-hexafluoropropylene) (FEP), poly(tetrafluoroethylene-propylene) (FEPM), poly(tetrafluoroethylene-perfluoropropylene vinyl ether), poly(tetrafluoroethylene-perfluoroalkyl vinyl ether) (PFA) (e.g., poly(tetrafluoroethylene-perfluoropropyl vinyl ether)), polyvinylidene fluoride (PVF), polyvinylidene fluoride (PVDF), poly(vinylidene fluoride-chlorotrifluoroethylene), perfluoropolyether, perfluorosulfonic acid, and perfluoropolyoxyheterocyclic butane, etc.
[0156] Fluoropolymers can also have structural units derived from fluorinated ethylene or fluorinated propylene.
[0157] Fluoropolymers can be used alone or in combination with two or more.
[0158] Fluoropolymers are preferably FEP, PFA, ETFE or PTFE.
[0159] FEP can be obtained under the trade name TEFLON FEP (registered trademark) from DuPont de Nemours, Inc., or NEOFLON FEP from Daikin Industries, Ltd. PFFA can be obtained under the trade name NEOFLON PFA from Daikin Industries, Ltd., TEFLON PFA (registered trademark) from DuPont de Nemours, Inc., or HYFLON PFA from Solvay Solexis Inc.
[0160] Fluoropolymers more preferably include PTFE. PTFE may also be a PTFE homopolymer, a partially modified PTFE homopolymer, or a combination thereof. The partially modified PTFE homopolymer preferably contains less than 1% by mass of structural units derived from comonomers other than tetrafluoroethylene, based on the total mass of the polymer.
[0161] Fluoropolymers can also be cross-linked fluoropolymers with cross-linking groups. Cross-linked fluoropolymers can be cross-linked using conventionally known cross-linking methods. A representative cross-linked fluoropolymer is a fluoropolymer with (meth)acryloyloxy groups. For example, a cross-linked fluoropolymer can be represented by the following formula:
[0162] H2C=CR'COO-(CH2) n -R-(CH2) n -OOCR'=CH2
[0163] In the formula, R is an oligomer chain containing structural units derived from fluorinated α-olefin monomers, R' is H or -CH3, and n is 1 to 4. R can also be a fluorinated oligomer chain containing structural units derived from tetrafluoroethylene.
[0164] A free radical crosslinking reaction is initiated via the (meth)acryloyloxy group on the fluoropolymer, thus exposing the fluoropolymer with the (meth)acryloyloxy group to a free radical source, thereby enabling the formation of a crosslinked fluoropolymer network structure. The free radical source is not particularly limited, but photoradical polymerization initiators or organic peroxides are preferred examples. Preferred photoradical polymerization initiators and organic peroxides are well known in the art. Crosslinkable fluoropolymers are commercially available, such as Viton B manufactured by DuPont de Nemours, Inc.
[0165] Polymers of compounds having cyclic aliphatic hydrocarbon groups and olefinically unsaturated groups-
[0166] Polymers that are compounds having cyclic aliphatic hydrocarbon groups and groups having olefinic unsaturated bonds, for example, include thermoplastic resins having structural units derived from cyclic olefin monomers such as norbornene or polycyclic norbornene monomers.
[0167] Polymers containing compounds having cyclic aliphatic hydrocarbon groups and olefinically unsaturated groups can be ring-opening polymers of the aforementioned cyclic olefins or hydrides of ring-opening copolymers using two or more cyclic olefins. They can also be addition polymers of cyclic olefins with aromatic compounds having olefinically unsaturated bonds, such as those of chain olefins or vinyl groups. Furthermore, polar groups can be introduced into polymers containing compounds having cyclic aliphatic hydrocarbon groups and olefinically unsaturated groups.
[0168] Polymers containing cyclic aliphatic hydrocarbon groups and olefinically unsaturated groups can be used alone or in combination with two or more groups.
[0169] As a cyclic aliphatic hydrocarbon group, the ring structure can be a single ring, a fused ring composed of two or more rings, or a bridging ring.
[0170] Examples of ring structures that represent cyclic aliphatic hydrocarbon groups include cyclopentane rings, cyclohexane rings, cyclooctane rings, isophorone rings, norcamphene rings, and dicyclopentane rings.
[0171] There are no particular limitations on the compounds having cyclic aliphatic hydrocarbon groups and olefinically unsaturated groups, and examples include (meth)acrylate compounds having cyclic aliphatic hydrocarbon groups, (meth)acrylamide compounds having cyclic aliphatic hydrocarbon groups, and vinyl compounds having cyclic aliphatic hydrocarbon groups. Among these, (meth)acrylate compounds having cyclic aliphatic hydrocarbon groups are preferably examples. Furthermore, compounds having cyclic aliphatic hydrocarbon groups and olefinically unsaturated groups can be monofunctional or polyfunctional olefinically unsaturated compounds.
[0172] In compounds containing cyclic aliphatic hydrocarbon groups and groups containing olefinic unsaturated bonds, the number of cyclic aliphatic hydrocarbon groups can be more than one or more.
[0173] The polymer of a compound having cyclic aliphatic hydrocarbon groups and olefin unsaturated groups can be a polymer formed by polymerizing a compound having at least one cyclic aliphatic hydrocarbon group and olefin unsaturated groups, a polymer of a compound having two or more cyclic aliphatic hydrocarbon groups and olefin unsaturated groups, or a copolymer of a compound with other olefin unsaturated compounds that do not have cyclic aliphatic hydrocarbon groups.
[0174] Furthermore, polymers containing cyclic aliphatic hydrocarbon groups and olefinically unsaturated groups are preferably cyclic olefin polymers.
[0175] -polyphenylene oxide-
[0176] When thermosetting occurs after film formation, from the viewpoint of heat resistance and film-forming properties, the weight-average molecular weight (Mw) of polyphenylene ether is preferably 500 to 5,000, more preferably 500 to 3,000. Furthermore, when thermosetting is not performed, the weight-average molecular weight is not particularly limited, but is preferably 3,000 to 100,000, more preferably 5,000 to 50,000.
[0177] From the viewpoint of dielectric loss tangent and heat resistance, the average number of phenolic hydroxyl groups (terminal hydroxyl number) at the molecular end of each molecule of polyphenylene ether is preferably 1 to 5, more preferably 1.5 to 3.
[0178] The number of terminal hydroxyl groups in polyphenylene ether is known, for example, according to the product specifications. Furthermore, the number of terminal hydroxyl groups is expressed, for example, as the average number of phenolic hydroxyl groups per molecule of all polyphenylene ethers present in 1 mole of polyphenylene ether.
[0179] Polyphenylene oxide can be used alone or in combination with two or more types.
[0180] Examples of polyphenylene ethers include, for example, polyphenylene ethers comprising at least one of 2,6-dimethylphenol and difunctional and trifunctional phenols, as well as poly(2,6-dimethyl-1,4-phenylene ether). More specifically, polyphenylene ethers are preferably compounds having a structure represented by the formula (PPE).
[0181] [Chemical Formula 1]
[0182]
[0183] In the formula (PPE), X represents an alkylene group with 1 to 3 carbon atoms or a single bond, m represents an integer from 0 to 20, n represents an integer from 0 to 20, and the sum of m and n represents an integer from 1 to 30.
[0184] As an example of the alkylene group in X above, dimethylmethylene can be cited.
[0185] -Aromatic polyetherketone-
[0186] As an aromatic polyetherketone, it is not particularly limited and can use known aromatic polyetherketones.
[0187] Aromatic polyetherketones are preferably polyetheretherketones.
[0188] Polyetheretherketone (PEEK) is a type of aromatic polyetherketone polymer, characterized by bonds arranged in the order of ether, ether, and carbonyl. These bonds are preferably linked by divalent aromatic groups.
[0189] Aromatic polyetherketones can be used alone or in combination with two or more.
[0190] Examples of aromatic polyetherketones include polyether etherketone (PEEK) having a chemical structure represented by the following formula (P1), polyetherketone (PEK) having a chemical structure represented by the following formula (P2), polyetherketone ketone (PEKK) having a chemical structure represented by the following formula (P3), polyether etherketone ketone (PEEKK) having a chemical structure represented by the following formula (P4), and polyetherketone etherketone ketone (PEKEKK) having a chemical structure represented by the following formula (P5).
[0191] [Chemical Formula 2]
[0192]
[0193] From the viewpoint of mechanical properties, n in each of formulas (P1) to (P5) is preferably 10 or more, more preferably 20 or more. On the other hand, from the viewpoint of ease of manufacturing aromatic polyetherketones, n is preferably 5,000 or less, more preferably 1,000 or less. That is, n is preferably 10 to 5,000, more preferably 20 to 1,000.
[0194] The polymer contained in the membrane involved in this invention is preferably a polymer that is soluble in a specific organic solvent (hereinafter also referred to as "soluble polymer").
[0195] Specifically, the soluble polymer in this invention is a polymer in which more than 0.1g is dissolved at 25°C in 100g of at least one solvent selected from N-methylpyrrolidone, N-ethylpyrrolidone, dichloromethane, dichloroethane, chloroform, N,N-dimethylacetamide, γ-butyrolactone, dimethylformamide, ethylene glycol monobutyl ether, and ethylene glycol monoethyl ether.
[0196] The membrane involved in this invention may contain only one polymer or may contain two or more polymers.
[0197] From the viewpoint of the dielectric loss tangent of the membrane and its adhesion to the metal, the polymer content relative to the total mass of the membrane is preferably 20% to 99% by mass, more preferably 30% to 98% by mass, even more preferably 40% to 97% by mass, and particularly preferably 50% to 95% by mass.
[0198] The membrane involved in this invention preferably contains filler.
[0199] -filler-
[0200] As a packing material, it can be granular or fibrous, and can be inorganic or organic.
[0201] In the membranes involved in this invention, from the viewpoint of suppressing deformation of the metal wiring when bonded to it, it is preferable that the number density of the filler inside is greater than that on the surface.
[0202] The number density of the packing material is measured by the following method.
[0203] Cut the membrane using a slicer to prepare a cross-sectional sample. Observe the cross-sectional sample using a scanning electron microscope (approximately 100x to 300x). Observe at least three locations to ensure the total observed area is 0.5 mm². 2 The above calculates the value per 1mm. 2 The number of fillers is taken as the average value.
[0204] Furthermore, when the membrane involved in the present invention comprises a polymer and a filler, it is preferable that the surface of the membrane contains a filler having an elastic modulus lower than that of the polymer, and it is preferable that the interior of the membrane contains a filler having an elastic modulus higher than that of the polymer.
[0205] As an inorganic filler, known inorganic fillers can be used.
[0206] Materials used as inorganic fillers include, for example, BN, Al2O3, AlN, TiO2, SiO2, barium titanate, strontium titanate, aluminum hydroxide, calcium carbonate, and materials containing two or more of these.
[0207] From the viewpoint of thermal expansion coefficient and adhesion to metal, the inorganic filler is preferably metal oxide particles or fibers, more preferably silicon dioxide particles, titanium dioxide particles or glass fibers, and especially preferably silicon dioxide particles or glass fibers.
[0208] From the viewpoint of thermal expansion coefficient and adhesion to metal, the average particle size of the inorganic filler is preferably 5 nm to 20 μm, more preferably 10 nm to 10 μm, even more preferably 20 nm to 1 μm, and particularly preferably 25 nm to 500 nm. When the particles or fibers are flat, the length in the short side direction is indicated.
[0209] As an organic filler, known organic fillers can be used.
[0210] Examples of materials that can be used as organic fillers include polyethylene, polystyrene, urea-formalin filler, polyester, cellulose, acrylic resin, fluororesin, cured epoxy resin, cross-linked benzoguanamine resin, cross-linked acrylic resin, liquid crystal polymer, and materials containing two or more of these.
[0211] Furthermore, the organic filler can be fibrous, such as nanofibers, or hollow resin particles.
[0212] From the viewpoint of thermal expansion coefficient and adhesion to metal, the organic filler is preferably fluoropolymer particles, polyester resin particles, polyethylene particles, liquid crystal polymer particles or cellulose resin nanofibers, and more preferably polytetrafluoroethylene particles, polyethylene particles or liquid crystal polymer particles.
[0213] Here, liquid crystal polymer particles can be manufactured, for example, by polymerizing a liquid crystal polymer and then pulverizing it using a pulverizer or the like to produce powder. The average particle size of the liquid crystal polymer particles is preferably smaller than the thickness of each layer.
[0214] From the viewpoint of thermal expansion coefficient and adhesion to metal, the average particle size of the organic filler is preferably 5 nm to 20 μm, more preferably 10 nm to 1 μm, even more preferably 20 nm to 500 nm, and especially preferably 25 nm to 90 nm.
[0215] The membrane involved in this invention can be a single-layer structure or a multi-layer structure. In the case of a single-layer structure, it is preferable to describe a change in elastic modulus from the interior to the surface where the composition changes.
[0216] The membrane involved in this invention has a layer A and a layer B disposed on at least one side of the layer A, wherein the elastic modulus of the surface of the layer B at 160°C is preferably less than the elastic modulus of the interior at 160°C.
[0217] Furthermore, the membrane involved in the present invention has a layer A and a layer B disposed on at least one side of the layer A, wherein the elastic modulus of the surface of the layer B at 300°C is preferably less than the elastic modulus of the interior at 300°C.
[0218] Layer B is preferably the surface layer (outermost layer). The elastic modulus of layer B at 160°C is preferably less than that of layer A at 160°C. Furthermore, the elastic modulus of layer B at 300°C is preferably less than that of layer A at 300°C.
[0219] In this invention, the "surface" of each layer refers to the region extending from the outermost surface of the layer to a position equivalent to 10% of the layer thickness when the layer thickness is 30 μm or less. When the layer thickness exceeds 30 μm, the "surface" refers to the region extending from the outermost surface of the layer to a position 3 μm away along the thickness direction.
[0220] In this invention, the "interior" of a layer refers to the region extending from the center of the layer in the thickness direction to a position equivalent to ±5% of the layer thickness when the layer thickness is 30 μm or less. When the layer thickness exceeds 30 μm, the "interior" refers to the region extending from the center of the layer in the thickness direction to a position ±1.5 μm away along the thickness direction.
[0221] <Layer A>
[0222] Layer A preferably contains a liquid crystal polymer. Layer A may contain only one type of liquid crystal polymer, or it may contain two or more types.
[0223] From the viewpoint of thermal expansion coefficient and adhesion to metal, the content of liquid crystal polymer in layer A is preferably 20% to 100% of the total volume of layer A, more preferably 20% to 90% of the total volume, even more preferably 30% to 80% of the total volume, and especially preferably 40% to 70% of the total volume.
[0224] From the viewpoint that the elastic modulus of layer A is greater than that of layer B, layer A preferably contains filler, more preferably contains filler with a melting point of 200°C or higher, and even more preferably contains inorganic filler.
[0225] The average particle size of the filler is preferably about 20% to about 40% of the thickness of layer A, for example, 25%, 30% or 35% of the thickness of layer A can also be selected.
[0226] Layer A may contain only one type of filler or two or more types.
[0227] From the viewpoint of thermal expansion coefficient and adhesion to metal, the filler content in layer A relative to the total volume of layer A is preferably 5% to 80% by volume, more preferably 10% to 70% by volume, even more preferably 20% to 70% by volume, and especially preferably 30% to 60% by volume.
[0228] Layer A may also contain other additives besides liquid crystal polymers and fillers.
[0229] Other additives can be well-known additives. Specifically, examples include leveling agents, defoamers, antioxidants, UV absorbers, flame retardants, and colorants.
[0230] Furthermore, layer A may also contain resins other than liquid crystal polymers as other additives.
[0231] Examples of resins other than liquid crystal polymers include polypropylene, polyamide, polyesters other than liquid crystal polyesters, polyphenylene sulfide, polyetherketone, polycarbonate, polyethersulfone, polyphenylene ether and its modified forms, polyetherimide and other thermoplastic resins other than liquid crystal polyesters; elastomers such as copolymers of glycidyl methacrylate and polyethylene; and thermosetting resins such as phenol resins, epoxy resins, polyimide resins, and cyanate ester resins.
[0232] The total content of other additives in layer A is preferably 25 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, relative to the content of the liquid crystal polymer of 100 parts by mass.
[0233] The average thickness of layer A is not particularly limited, but from the viewpoint of thermal expansion coefficient and adhesion to the metal, it is preferably 5 μm to 90 μm, more preferably 10 μm to 70 μm. Particularly preferred is 15 μm to 50 μm.
[0234] The method for measuring the average thickness of each layer in the membrane involved in this invention is as follows.
[0235] The film was cut using a slicer, and the cross-section was observed using an optical microscope to evaluate the thickness of each layer. At least three sections were cut from each section, and the thickness was measured at at least three points on each section. The average thickness was then taken as the mean thickness.
[0236] The dielectric loss tangent of layer A is preferably 0.005 or less, and more preferably more than 0 and less than 0.003.
[0237] <Layer B>
[0238] Layer B preferably contains a liquid crystal polymer.
[0239] Except as described below, the preferred method for the liquid crystal polymer used in layer B is the same as that for the liquid crystal polymer used in layer A.
[0240] The liquid crystal polymer contained in layer B may be the same as or different from the liquid crystal polymer contained in layer A. From the viewpoint that the elastic modulus of layer B is less than that of layer A, layer B preferably contains a liquid crystal polymer with an elastic modulus lower than that of the liquid crystal polymer contained in layer A.
[0241] From the perspective of thermal expansion coefficient and adhesion to metal, the content of liquid crystal polymer in layer B is preferably greater than that in layer A.
[0242] Furthermore, from the viewpoint of thermal expansion coefficient and adhesion to metal, the content of liquid crystal polymer in layer B relative to the total volume of layer B is preferably 50% to 100% by volume, more preferably 80% to 100% by volume, even more preferably 90% to 100% by volume, and especially preferably 95% to 100% by volume.
[0243] From the viewpoint that the elastic modulus of layer B is less than that of layer A, layer B preferably contains filler, more preferably contains filler with a melting point of less than 300°C, and even more preferably contains organic filler.
[0244] Layer B may contain only one type of filler or two or more types.
[0245] From the viewpoint of thermal expansion coefficient and adhesion to metal, the filler content in layer B relative to the total volume of layer B is preferably 5% to 80% by volume, more preferably 10% to 70% by volume, even more preferably 20% to 70% by volume, and especially preferably 30% to 60% by volume.
[0246] Layer B may also contain other additives besides liquid crystal polymers and fillers.
[0247] The preferred method for other additives used in layer B is the same as that for other additives used in layer A.
[0248] From the perspective of thermal expansion coefficient and adhesion to metal, the average thickness of layer B is preferably thinner than the average thickness of layer A.
[0249] From the perspective of thermal expansion coefficient and adhesion to metal, the average thickness T of layer A is... A With the average thickness T of layer B B The ratio of T A / T B The value of is preferably greater than 1, more preferably 2 to 100, even more preferably 2.5 to 20, and especially preferably 3 to 10.
[0250] Furthermore, the average thickness of layer B can be arbitrarily set according to the thickness of the metal adhered to layer B, but from the viewpoint of adhesion to the metal, it is preferable to be thicker than the thickness of the metal. Specifically, the average thickness of layer B is preferably 0.1 μm to 20 μm, more preferably 0.5 μm to 15 μm, even more preferably 1 μm to 10 μm, and particularly preferably 3 μm to 8 μm.
[0251] The dielectric loss tangent of layer B is preferably 0.01 or less, more preferably greater than 0 and less than 0.005. The dielectric loss tangent of layer B can be evaluated by removing layers other than layer B from the film. Depending on the situation, layer B can also be removed from the film and evaluated using the resulting powdered sample.
[0252] As preferred methods in layers A and B, the following methods (1) to (4) and any combination of methods (1) to (3) and method (4) can be cited.
[0253] (1) Layer A contains filler with a melting point of 200°C or higher (preferably inorganic filler, more preferably inorganic oxide filler, and especially preferably silica particles).
[0254] (2) Layer B contains filler with a melting point of less than 300°C (preferably organic filler, more preferably polyolefin filler, and especially preferably polyethylene filler).
[0255] (3) Layer A contains filler with a melting point of 200°C or higher (preferably inorganic filler, more preferably inorganic oxide filler, especially silica particles), and layer B contains filler with a melting point of less than 300°C (preferably organic filler, more preferably polyolefin filler, especially polyethylene filler).
[0256] (4) Layer B contains a liquid crystal polymer with a lower elastic modulus than the liquid crystal polymer contained in layer A.
[0257] From the viewpoint of thermal expansion coefficient and adhesion to metal, the film involved in the present invention preferably has layer C in addition to the above-mentioned layer A and layer B, and more preferably has the above-mentioned layer B, layer A and layer C in sequence.
[0258] <Layer C>
[0259] Layer C is preferably a surface layer (outermost layer), and more preferably a surface layer on the side to which the metal is attached.
[0260] Furthermore, when the film involved in the present invention is used as a laminate having a metal layer (e.g., metal foil or metal wiring), layer C is preferably disposed between the metal layer and layer A.
[0261] From the viewpoint of thermal expansion coefficient and adhesion to metal, layer C preferably contains a liquid crystal polymer.
[0262] Except as described below, the preferred method for the liquid crystal polymer used in layer C is the same as that for the liquid crystal polymer used in layer A.
[0263] The liquid crystal polymer contained in layer C may be the same as or different from the liquid crystal polymer contained in layer A or layer B, but it is preferred that it be the same as the liquid crystal polymer contained in layers A and B.
[0264] From the viewpoint of thermal expansion coefficient and adhesion to metal, the content of liquid crystal polymer in layer C is preferably greater than the content of liquid crystal polymer in layer A.
[0265] Furthermore, from the viewpoint of thermal expansion coefficient and adhesion to metal, the content of liquid crystal polymer in layer C relative to the total volume of layer C is preferably 50% to 100% by volume, more preferably 80% to 100% by volume, even more preferably 90% to 100% by volume, and especially preferably 95% to 100% by volume.
[0266] Layer C may also contain filler.
[0267] Except as described below, the preferred method for the packing material used in layer C is the same as that for the packing material used in layer A.
[0268] From the perspective of thermal expansion coefficient and adhesion to metal, the filler content in layer C is preferably less than that in layer A.
[0269] Furthermore, from the viewpoint of thermal expansion coefficient and adhesion to metal, the filler content in layer C is preferably not containing filler or is more than 0% by volume and less than 20% by volume relative to the total volume of layer C, more preferably not containing filler or is more than 0% by volume and less than 10% by volume relative to the total volume of layer C, even more preferably not containing filler or is more than 0% by volume and less than 5% by volume relative to the total volume of layer C, and especially preferably not containing filler.
[0270] Layer C may also contain other additives besides liquid crystal polymers and fillers.
[0271] The preferred methods for other additives used in layer C are the same as those for other additives used in layer A.
[0272] From the perspective of thermal expansion coefficient and adhesion to metal, the average thickness of layer C is preferably thinner than the average thickness of layer A.
[0273] From the perspective of thermal expansion coefficient and adhesion to metal, the average thickness T of layer A is... A With the average thickness T of layer C C The ratio of T A / T C The value of is preferably greater than 1, more preferably 2 to 100, even more preferably 2.5 to 20, and especially preferably 3 to 10.
[0274] Furthermore, from the perspective of thermal expansion coefficient and adhesion to metal, the average thickness T of layer C is... C With the average thickness T of layer B B The ratio of T C / T B The value is preferably 0.2 to 5, more preferably 0.5 to 2, and especially preferably 0.8 to 1.2.
[0275] Furthermore, from the viewpoint of thermal expansion coefficient and adhesion to metal, the average thickness of layer C is preferably 0.1 μm to 20 μm, more preferably 0.5 μm to 15 μm, even more preferably 1 μm to 10 μm, and particularly preferably 3 μm to 8 μm.
[0276] The dielectric loss tangent of layer C is preferably 0.005 or less, more preferably greater than 0 and less than 0.003. The dielectric loss tangent of layer C can be evaluated by removing layers other than layer C from the film. Depending on the situation, layer C can also be removed from the film and evaluated using the resulting powdered sample.
[0277] From the viewpoint of strength and electrical characteristics (characteristic impedance) when the film is laminated with a metal layer, the average thickness of the film involved in the present invention is preferably 6 μm to 500 μm, more preferably 6 μm to 100 μm, and especially preferably 12 μm to 100 μm.
[0278] Regarding the average thickness of the film, measurements were taken at any 5 points using an adhesive film thickness gauge, such as an electronic micrometer (product name "KG3001A", manufactured by ANRITSU CORPORATION), and the average value was recorded.
[0279] <Membrane Manufacturing Methods>
[0280] (Membrane fabrication)
[0281] The method for manufacturing the membrane involved in this invention is not particularly limited and can be referred to from known methods.
[0282] Methods for manufacturing the film according to the present invention include, for example, casting, coating, and extrusion. Casting is particularly preferred for thinner films, and co-extrusion is particularly preferred for thicker films. Furthermore, when the film according to the present invention has a multilayer structure, co-casting, multilayer coating, and co-extrusion are preferred, for example. Co-casting is particularly preferred.
[0283] When manufacturing a multilayer structure in a film by co-casting or multilayer coating, it is preferable to use a layer A forming composition, a layer B forming composition, and a layer C forming composition, in which the components of each layer are dissolved or dispersed in a solvent, for co-casting or multilayer coating.
[0284] Examples of solvents include, for instance, halogenated hydrocarbons such as dichloromethane, chloroform, 1,1-dichloroethane, 1,2-dichloroethane, 1,1,2,2-tetrachloroethane, 1-chlorobutane, chlorobenzene, and o-dichlorobenzene; halogenated phenols such as p-chlorophenol, pentachlorophenol, and pentafluorophenol; ethers such as diethyl ether, tetrahydrofuran, and 1,4-dioxane; ketones such as acetone and cyclohexanone; esters such as ethyl acetate and γ-butyrolactone; carbonates such as ethylene carbonate and propylene carbonate; amines such as triethylamine; nitrogen-containing heterocyclic aromatic compounds such as pyridine; nitrile compounds such as acetonitrile and succinate; amides such as N,N-dimethylformamide and N,N-dimethylacetamide and N-methylpyrrolidone; urea compounds such as tetramethylurea; nitro compounds such as nitromethane and nitrobenzene; sulfur compounds such as dimethyl sulfoxide and sulfolane; and phosphorus compounds such as hexamethylphosphonamide and tri-n-butylphosphonic acid. Two or more of the aforementioned substances may be used.
[0285] As a solvent, from the viewpoint of low corrosivity and ease of handling, aprotic compounds are preferred, especially aprotic compounds containing no halogen atoms. The proportion of the aprotic compound in the total solvent is preferably 50% to 100% by mass, more preferably 70% to 100% by mass, and particularly preferably 90% to 100% by mass. Furthermore, from the viewpoint of readily dissolving liquid crystal polymers, the aforementioned aprotic compound is preferably an amide such as N,N-dimethylformamide, N,N-dimethylacetamide, tetramethylurea, or N-methylpyrrolidone, or an ester such as γ-butyrolactone, more preferably N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.
[0286] Furthermore, as a solvent, from the viewpoint of easily dissolving liquid crystal polymers, it is preferable to include a compound with a dipole moment of 3 to 5. The proportion of the compound with a dipole moment of 3 to 5 in the total solvent is preferably 50% to 100% by mass, more preferably 70% to 100% by mass, and particularly preferably 90% to 100% by mass.
[0287] As the aforementioned aprotic compounds, compounds with a dipole moment of 3 to 5 are preferred.
[0288] Furthermore, from the viewpoint of easy removal, the solvent preferably contains a compound with a boiling point of 220°C or less at 1 atm, and the proportion of the compound with a boiling point of 220°C or less at 1 atm in the total solvent is preferably 50% to 100% by mass, more preferably 70% to 100% by mass, and especially preferably 90% to 100% by mass.
[0289] As the aforementioned aprotic compound, it is preferable to use a compound with a boiling point of 220°C or less at 1 atmosphere.
[0290] Furthermore, in the case where the membrane manufacturing method of the present invention is manufactured by the above-mentioned co-casting method, multilayer coating method, and co-extrusion method, a support body can be used.
[0291] Examples of supports include metal rollers, metal strips, glass plates, resin films, and metal foils. Among these, metal rollers, metal strips, or resin films are preferred.
[0292] Examples of resin films include, for instance, polyimide (PI) films. Commercially available examples of resin films include Upilex S and Upilex R manufactured by UBE Corporation, Kapton manufactured by DU PONT-TORAY CO., LTD., and IF30, IF70, and LV300 manufactured by SKC Kolon PI, Inc.
[0293] Furthermore, a surface treatment layer can be formed on the surface of the support to facilitate easy peeling. As a surface treatment layer, hard chrome plating, fluoropolymer resin, etc., can be used.
[0294] The average thickness of the support is not particularly limited, but it is preferably 25 μm or more and 75 μm or less, more preferably 50 μm or more and 75 μm or less.
[0295] Furthermore, the method for removing at least a portion of the solvent from the cast or coated film composition (coating) is not particularly limited, and known drying methods can be used.
[0296] (Stretching)
[0297] From the viewpoint of controlling molecular orientation, adjusting the coefficient of thermal expansion, and mechanical properties, the membranes involved in this invention can be appropriately combined for stretching. The stretching method is not particularly limited and can be carried out using known methods, either in a solvent-containing state or in a dry film state. Stretching in a solvent-containing state can be performed by holding the membrane to elongate it, or it can be performed without elongation by utilizing the self-shrinkage caused by drying. Stretching is particularly effective in improving elongation at break or tensile strength when the membrane's brittleness is reduced due to the addition of inorganic fillers, etc.
[0298] (Heat treatment)
[0299] The membrane manufacturing method involved in this invention preferably includes a step of heat treatment (annealing) of the membrane after membrane formation.
[0300] From the viewpoint of dielectric loss tangent and peel strength, the heat treatment temperature in the above-mentioned heat treatment process is preferably 260°C to 370°C, more preferably 280°C to 360°C, and even more preferably 300°C to 350°C. The heat treatment time is preferably 15 minutes to 10 hours, and even more preferably 30 minutes to 5 hours.
[0301] Furthermore, the membrane manufacturing method of the present invention may also include other known processes as needed.
[0302] <Application>
[0303] The membrane involved in this invention can be used for various purposes. It is preferably used for electronic components such as printed wiring boards, and more preferably for flexible printed circuit boards.
[0304] Furthermore, the membrane involved in this invention can preferably be used as a metal bonding membrane.
[0305] (Layered structure)
[0306] The laminated body involved in this invention is any laminated body formed by stacking the film involved in this invention. Preferably, the laminated body involved in this invention has the film involved in this invention and a metal layer disposed on the surface of the film on the side of layer A; more preferably, the metal layer is a copper layer. Since the metal layer is disposed on the surface of layer A, layer B is the outermost layer in the laminated body.
[0307] Furthermore, the laminated body according to the present invention preferably has the film according to the present invention and a metal layer disposed on the surface of the film on the side of layer B, and more preferably the metal layer is a copper layer.
[0308] The metal layer disposed on the surface of layer B is preferably a metal layer disposed on the surface of layer B.
[0309] Furthermore, the laminated body according to the present invention preferably has a film according to the present invention having layer B, layer A and layer C in sequence, a metal layer of the film disposed on the side of layer B, and a metal layer of the film disposed on the side of layer C, and more preferably all of the above metal layers are copper layers.
[0310] Preferably, the metal layer disposed on the surface of layer C is a metal layer disposed on the surface of layer C. More preferably, the metal layer disposed on the surface of layer B is a metal layer disposed on the surface of layer B, and the metal layer disposed on the surface of layer C is a metal layer disposed on the surface of layer C.
[0311] Furthermore, the metal layer disposed on the surface of layer B and the metal layer disposed on the surface of layer C can be metal layers of the same material, thickness, and shape, or they can be metal layers of different materials, thicknesses, and shapes. From the viewpoint of adjusting characteristic impedance, the metal layer disposed on the surface of layer B and the metal layer disposed on the surface of layer C can be metal layers of different materials and thicknesses, or a metal layer can be stacked only on one side of layer B or layer C.
[0312] Furthermore, from the viewpoint of adjusting characteristic impedance, it is also preferable to stack a metal layer on one side of layer B or layer C and stack other films (preferably other liquid crystal polymer films) on the other sides.
[0313] When the metal layer disposed on the side of layer B is a copper layer disposed on the surface of layer B, the peel strength between layer B and the copper layer is preferably 0.5 kN / m or more, more preferably 0.7 kN / m or more, even more preferably 0.7 kN / m to 2.0 kN / m, and particularly preferably 0.9 kN / m to 1.5 kN / m.
[0314] Furthermore, when the metal layer disposed on the side of the aforementioned layer C is a copper layer disposed on the surface of the aforementioned layer C, the peel strength between the aforementioned layer C and the aforementioned copper layer is preferably 0.5 kN / m or more, more preferably 0.7 kN / m or more, even more preferably 0.7 kN / m to 2.0 kN / m, and particularly preferably 0.9 kN / m to 1.5 kN / m.
[0315] In this invention, the peel strength between layer B or layer C of the film and the metal layer (e.g., copper layer) is measured by the following method.
[0316] A 1.0 cm wide peel test piece was prepared from the laminate of the membrane and the metal layer. The membrane was fixed on a flat plate with double-sided tape. The strength (kN / m) of peeling the metal layer from the membrane at a speed of 50 mm / min was measured by the 180° method according to JIS C 5016 (1994).
[0317] The metal layer is preferably a copper layer. As the copper layer, rolled copper foil formed by rolling or electrolytic copper foil formed by electrolysis is preferred, and rolled copper foil is more preferred from the viewpoint of bending resistance.
[0318] The average thickness of the metal layer (preferably a copper layer) is not particularly limited, but is preferably 2 μm to 20 μm, more preferably 3 μm to 18 μm, and even more preferably 5 μm to 12 μm. The metal layer can be a carrier-supported metal layer that is peelably formed on the support (carrier). Known carriers can be used as the carrier. The average thickness of the carrier is not particularly limited, but is preferably 10 μm to 100 μm, more preferably 18 μm to 50 μm.
[0319] From the viewpoint of suppressing deformation of the metal wiring when bonding with it, the thickness of layer B is preferably greater than the thickness of the metal layer (e.g., copper layer).
[0320] The metal layer in the laminate involved in this invention can also be a metal layer with a circuit pattern.
[0321] It is also preferable to process the metal layers in the laminate involved in the present invention into the desired circuit pattern, for example by etching, and to set it as a flexible printed circuit board. There are no particular limitations on the etching method, and known etching methods can be used.
[0322] Example
[0323] The present invention will be described in more detail below with examples. The materials, amounts, proportions, processing contents, and processing order shown in the following examples can be appropriately modified without departing from the spirit of the invention. Therefore, the scope of the present invention is not limited to the specific examples shown below.
[0324] <<Measurement Methods>>
[0325] [Dielectric loss tangent]
[0326] The dielectric loss tangent was measured using the resonant perturbation method at a frequency of 10 GHz. A 10 GHz cavity resonator (KANTO Electronic Application and Development Inc. CP531) was connected to a network analyzer (E8363B, manufactured by Agilent Technology). A sample of the film (width: 2.0 mm × length: 80 mm) was inserted into the cavity resonator. Under conditions of 25°C and 60% RH, the dielectric loss tangent of the film was measured based on the change in resonant frequency before and after insertion over 96 hours.
[0327] [Elastic modulus and loss tangent]
[0328] A UV resin-coated film was used to cut a cross-sectional sample for evaluation. Then, the sample was observed in VE-AFM mode using a scanning probe microscope (SPA400, manufactured by Seiko Instruments Inc.) to calculate the surface and internal storage modulus and loss tangent (loss modulus / storage modulus).
[0329] Coefficient of thermal expansion
[0330] Using a thermomechanical analysis (TMA) apparatus, a tensile load of 1g was applied to both ends of a membrane with a width of 5mm and a length of 20mm. After heating to 25℃~200℃ at a rate of 5℃ / min, it was cooled to 30℃ at a rate of 20℃ / min, and then heated again at a rate of 5℃ / min. The coefficient of thermal expansion (=the coefficient of expansion of the membrane) was calculated based on the slope of the TMA curve between 30℃ and 150℃ at this point.
[0331] [Peel strength]
[0332] A 1.0 cm wide peel test piece was prepared from the laminate of the film and copper foil. The film was fixed to a flat plate with double-sided tape. The peel strength (kN / m) when peeling the copper foil from the film at a speed of 50 mm / min was measured according to JIS C 5016 (1994) using the 180° method. The peel strength of the film layer B side to the copper foil was evaluated by fixing the side opposite to layer B with double-sided tape. The peel strength of the film layer C side to the copper foil was evaluated by fixing the side opposite to layer C with double-sided tape.
[0333] <<Manufacturing Example>>
[0334] <Polymer>
[0335] LC-A: A liquid crystal polymer manufactured according to the following method
[0336] -LC-A Manufacturing-
[0337] 940.9 g (5.0 mol) of 6-hydroxy-2-naphthoic acid, 377.9 g (2.5 mol) of 4-hydroxyacetaminophen, 415.3 g (2.5 mol) of isophthalic acid, and 867.8 g (8.4 mol) of acetic anhydride were added to a reactor equipped with a stirring device, a torque meter, a nitrogen inlet pipe, a thermometer, and a reflux cooler. After replacing the gas in the reactor with nitrogen, the reactor was heated from room temperature (23°C) to 140°C over 60 minutes with stirring under a nitrogen flow, and then refluxed at 140°C for 3 hours.
[0338] Next, while distilling the byproducts acetic acid and unreacted acetic anhydride, the temperature was increased from 150°C to 300°C over 5 hours. After maintaining this temperature at 300°C for 30 minutes, the contents were removed from the reactor and cooled to room temperature. The resulting solid material was then pulverized to obtain powdered liquid crystal polyester (A1). The flow initiation temperature of this liquid crystal polyester (A1) was 193.3°C.
[0339] The liquid crystal polyester (A1) obtained above was heated from room temperature to 160°C in a nitrogen atmosphere for 2 hours and 20 minutes, then heated from 160°C to 180°C for 3 hours and 20 minutes, and held at 180°C for 5 hours to induce solid-state polymerization. After cooling, the product was pulverized using a pulverizer to obtain powdered liquid crystal polyester (A2). The flow initiation temperature of this liquid crystal polyester (A2) was 220°C.
[0340] The liquid crystal polyester (A2) obtained above was heated from room temperature (23°C) to 180°C in a nitrogen atmosphere for 1 hour and 25 minutes, then heated from 180°C to 255°C for 6 hours and 40 minutes, and held at 255°C for 5 hours to induce solid-state polymerization. After cooling, powdered liquid crystal polyester (A) (LC-A) was obtained. The flow initiation temperature of the liquid crystal polyester (B) was 302°C. Furthermore, the melting point of the liquid crystal polyester (A) was measured to be 311°C using differential scanning calorimetry.
[0341] LC-B: A liquid crystal polymer manufactured according to the following method
[0342] -LC-B Manufacturing-
[0343] 940.9 g (5.0 mol) of 6-hydroxy-2-naphthoic acid, 377.9 g (2.5 mol) of 4-hydroxyacetaminophen, 415.3 g (2.5 mol) of isophthalic acid, and 867.8 g (8.4 mol) of acetic anhydride were added to a reactor equipped with a stirring device, a torque meter, a nitrogen inlet pipe, a thermometer, and a reflux cooler. After replacing the gas in the reactor with nitrogen, the reactor was heated from room temperature (23°C) to 143°C over 60 minutes with stirring under a nitrogen flow, and then refluxed at 143°C for 1 hour.
[0344] Next, while distilling the byproducts acetic acid and unreacted acetic anhydride, the temperature was increased from 150°C to 300°C over 5 hours. After maintaining this temperature at 300°C for 30 minutes, the contents were removed from the reactor and cooled to room temperature. The resulting solid material was then pulverized to obtain powdered liquid crystal polyester (B1). The flow initiation temperature of this liquid crystal polyester (B1) was 191°C.
[0345] The liquid crystal polyester (B1) obtained above was heated from room temperature to 160°C in a nitrogen atmosphere for 2 hours and 20 minutes, then heated from 160°C to 180°C for 3 hours and 20 minutes, and held at 180°C for 5 hours to induce solid-state polymerization. After cooling, the product was pulverized using a pulverizer to obtain powdered liquid crystal polyester (B2). The flow initiation temperature of this liquid crystal polyester (B2) was 220°C.
[0346] The liquid crystal polyester (B2) obtained above was heated from room temperature (23°C) to 180°C in a nitrogen atmosphere for 1 hour and 20 minutes, then heated from 180°C to 240°C for 5 hours and held at 240°C for 5 hours to induce solid-state polymerization. After cooling, powdered liquid crystal polyester (B) (LC-B) was obtained. The flow initiation temperature of the liquid crystal polyester (B) was 285°C.
[0347] LC-C: A liquid crystal polymer manufactured according to the following method
[0348] -LC-C Manufacturing-
[0349] In a reactor equipped with a stirrer, torque meter, nitrogen inlet pipe, thermometer, and reflux cooler, 1034.99 g (5.5 mol) of 6-hydroxy-2-naphthoic acid, 378.33 g (1.75 mol) of 2,6-naphthoic acid, 83.07 g (0.5 mol) of terephthalic acid, 272.52 g (2.475 mol) of hydroquinone (0.225 mol excess relative to the total molar amount of 2,6-naphthoic acid and terephthalic acid), 1226.87 g (12 mol) of acetic anhydride, and 0.17 g of 1-methylimidazole as a catalyst were added. After replacing the gas in the reactor with nitrogen, the reactor was heated from room temperature to 145°C over 15 minutes under nitrogen flow while stirring, and then refluxed at 145°C for 1 hour.
[0350] Next, while distilling the incidentally generated acetic acid and unreacted acetic anhydride, the temperature was increased from 145°C to 310°C over 3 hours and 30 minutes. After maintaining the temperature at 310°C for 3 hours, the solid liquid crystal polyester (C1) was removed and cooled to room temperature. The flow initiation temperature of this polyester (C1) was 265°C.
[0351] [Manufacturing of Liquid Crystal Polyester Microparticles (LC-C)]
[0352] Liquid crystal polyester (C1) was pulverized using a jet mill (Kurimoto, Ltd.'s "KJ-200") to obtain liquid crystal polyester microparticles (LC-C). The average particle size of these liquid crystal polyester microparticles was 9 μm.
[0353] LC-D: Liquid crystal polymer manufactured according to the following method
[0354] -LC-D Manufacturing-
[0355] In a reactor equipped with a stirring device, torque meter, nitrogen inlet pipe, thermometer and reflux cooler, 941g (5.0 mol) of 6-hydroxy-2-naphthoic acid, 273g (2.5 mol) of 4-aminophenol, 415g (2.5 mol) of isophthalic acid and 1123g (11 mol) of acetic anhydride were added. After replacing the gas in the reactor with nitrogen, the mixture was stirred under a nitrogen flow and heated from room temperature (23°C) to 150°C over 15 minutes, and then refluxed at 150°C for 3 hours.
[0356] Next, while distilling the byproducts acetic acid and unreacted acetic anhydride, the temperature was increased from 150°C to 320°C over 3 hours and maintained until the viscosity increase was confirmed. The contents were then removed from the reactor and cooled to room temperature. The resulting solid material was pulverized using a pulverizer to obtain powdered liquid crystal polyester (D1).
[0357] The liquid crystal polyester (D1) obtained above was subjected to solid-state polymerization at 250°C for 3 hours under a nitrogen atmosphere. After cooling, it was pulverized using a pulverizer to obtain powdered liquid crystal polyester (LC-D).
[0358] [Polyphenylene ether]
[0359] P-1: A mixture of commercially available polyphenylene ether granules (SA120, manufactured by SABIC Corporation, weight average molecular weight Mw2, 600) / bisphenol A type epoxy resin (EPICLON850S, manufactured by DIC Corporation, average number of epoxy groups 2) / bisphenol A type cyanate ester resin (Badcy, manufactured by Lonza KK) / aromatic condensed phosphate ester (PX-200, manufactured by DAIHACHI CHEMICAL INDUSTRY CO., LTD.) / aluminum triethylphosphonate (EXOLIT OP-935, manufactured by Clariant (Japan) KK) / zinc octanoate = 25 / 34 / 25 / 8 / 8 / 0.01 (mass ratio)
[0360] <Cureable Compounds>
[0361] M-1: Commercially available aminophenol type epoxy resin (jER630LSD, manufactured by Mitsubishi Chemical Corporation) is used to achieve the amount of solids listed in Table 1.
[0362] M-2: A commercially available thermosetting resin (SLK, manufactured by Shin-Etsu Chemical Co., Ltd., which mainly contains polymer-type curing compounds) is used to achieve the amount of solids listed in Table 1.
[0363] <packing>
[0364] A-1: Using commercially available ultra-high molecular weight polyethylene microparticles (MIPELON PM200, manufactured by Mitsui Chemicals, Inc.) with an average particle size of 10 μm, the solid content is made to the amount described in Table 1.
[0365] F-1: Using a commercially available aqueous silica sol (MEK-ST-L, 30% by mass solids, methyl ethyl ketone (MEK) solvent, manufactured by Nissan Chemical Corporation) with an average particle size of 45 nm, the amount of solids was made to the amount described in Table 1.
[0366] F-2: Using commercially available silica microparticles (SO-C2, manufactured by ADMATECHS COMPANY LIMITED) with an average particle size of 0.5 μm, the solid content is made to the amount described in Table 1.
[0367] F-3: Use a mixture of LC-C and F-2 (mass ratio 1:1) to achieve the amount of solids as recorded in Table 1.
[0368] F-4: The solvent for commercially available polytetrafluoroethylene (PTFE) nanoparticles (POLYFLON PTFE D-210C, average particle size 0.25 μm, manufactured by Daikin Industries, Ltd.) was replaced with N-methylpyrrolidone solvent to achieve the amount of solids in the liquid crystal polymer film as described in Table 1.
[0369] F-5: Poly(tetrafluoroethylene) and perfluoroalkoxyethylene (PFA) copolymer particles, melting point 280℃, average particle size 0.2μm~0.5μm, dielectric loss tangent 0.001.
[0370] F-6: Commercially available hollow powder with an average particle size of 16μm (Glass Bubbles iM30K, manufactured by 3M Japan Limited).
[0371] F-7: Boron nitride particles, melting point >500℃, HP40MF100 (manufactured by Mizushima Ferroalloy Co., Ltd.), dielectric loss tangent of 0.0007.
[0372] <Membrane Formation>
[0373] Films were prepared according to the following co-casting or multilayer coating methods.
[0374] [Co-casting (solution film formation)]
[0375] -Preparation of polymer solution-
[0376] The above-mentioned liquid crystal polymer and additives were added to N-methylpyrrolidone and stirred at 140°C for 4 hours under a nitrogen atmosphere to obtain a liquid crystal polymer solution. The liquid crystal polymer and additives were added at the volume ratios listed in Table 1. The solid content concentrations of the solutions for layer B (surface layer), layer A (core layer), and layer C (support layer) were set to the concentrations listed in Table 1, respectively.
[0377] Next, the solution was first passed through a sintered fiber metal filter with a nominal pore size of 10 μm, and then again through a sintered fiber metal filter with a nominal pore size of 10 μm to obtain each liquid crystal polymer solution.
[0378] Alternatively, in the case where the additive is insoluble in N-methylpyrrolidone, a liquid crystal polymer solution is prepared without the additive. After passing through the sintered fiber metal filter described above, the additive is added and the solution is stirred.
[0379] - Fabrication of single-sided copper-clad laminates (Examples 1-4, Comparative Example 1)-
[0380] The obtained polymer solutions for layers A and B were fed into a casting die equipped with feed blocks and adjusted for co-casting, allowing it to be cast onto the treated surface of a copper foil (manufactured by FUKUDA METAL FOIL & POWDER CO., LTD., CF-T9DA-SV-12, average thickness 12 μm) to bring the copper foil into contact with layer A. The solvent was removed from the cast film by drying at 40°C for 4 hours. Furthermore, by holding at 300°C for 3 hours under a nitrogen atmosphere, a laminate (single-sided copper-clad laminate) with copper layers and a film was obtained.
[0381] -Fabrication of double-sided copper-clad laminates-
[0382] (Pre-processing of copper-clad laminate)
[0383] Compared to single-sided copper-clad laminates, a precursor for double-sided copper-clad laminates was obtained by placing the copper foil (manufactured by FUKUDA METAL FOIL & POWDER CO., LTD., CF-T9DA-SV-12, average thickness 12 μm) in contact with the film and laminating it for 1 minute using a laminator (Nikko-Materials Co., Ltd. "Vacuum Laminator V-130") at 140°C and a lamination pressure of 0.4 MPa.
[0384] - Fabrication of single-sided copper-clad laminates (Examples 5 to 20) -
[0385] The obtained polymer solutions for layer B (surface layer), layer A (core layer), and layer C (support layer) are fed into a casting die equipped with feed blocks and adjusted for co-casting. This allows the solution to be cast onto the treated surface of a copper foil (manufactured by FUKUDA METAL FOIL & POWDER CO., LTD., CF-T9DA-SV-18, average thickness 18 μm) to bring the copper foil into contact with layer C. The solvent is removed from the cast film by drying at 40°C for 4 hours, and then held at 300°C for 3 hours under a nitrogen atmosphere, thereby obtaining a laminate (single-sided copper-clad laminate) with copper layers and a film.
[0386] [Multi-layer coating]
[0387] -Preparation of polymer solution-
[0388] The polymers and additives listed in Table 1 were added to toluene, and the mixture was stirred for 60 minutes to obtain polymer solutions for layer A and layer B, respectively.
[0389] - Fabrication of single-sided copper-clad laminate (Example 21)-
[0390] On the treated surface of a copper foil (manufactured by FUKUDA METAL FOIL & POWDER CO., LTD., CF-T9DA-SV-18, 18 μm thick, surface roughness Rz0.85 μm of the treated surface), polymer solutions for layer A and layer B were fed into a slot die coater equipped with a sliding coating machine for multi-layer coating. After drying at 100°C for 3 minutes, the solvent was removed from the coating by drying at 170°C for 3 minutes. Then, the temperature was increased from room temperature to 200°C at a rate of 1°C / min and held at this temperature for 2 hours to obtain a laminate with copper layers (single-sided copper-clad laminate).
[0391] (This hot pressing process)
[0392] Using a hot press machine (Toyo Seiki Seisaku-sho, Ltd. manufactures "MP-SNL"), the obtained copper-clad laminate precursor is hot-pressed at 300°C and 4.5 MPa for 10 minutes to produce a double-sided copper-clad laminate.
[0393] Fabrication of Flexible Wiring Boards
[0394] Using the above-mentioned single-sided copper-clad laminate and the above-mentioned double-sided copper-clad laminate, a flexible wiring substrate with a four-layer stripline structure having an outer plane (grounding layer) was fabricated.
[0395] (The process of forming the wiring substrate)
[0396] Using a known photosensitive etching process, the copper foil of the aforementioned double-sided copper-clad laminate was patterned to create a wiring substrate containing three pairs of signal lines. The signal lines were set to a length of 100 mm and a width with a characteristic impedance of 50 Ω.
[0397] (Layering process)
[0398] Using the aforementioned wiring substrate and a pair of the aforementioned single-sided copper-clad laminates, a single-sided copper-clad laminate / wiring substrate / single-sided copper-clad laminate is formed by overlapping them such that the film side of the single-sided copper-clad laminate is in contact with the wiring substrate. A flexible wiring substrate is fabricated by laminating the laminates using a vacuum pressurization apparatus at the pressurization temperatures listed in Table 1.
[0399] The wiring deformation was evaluated using the fabricated flexible wiring substrate. The evaluation method is described below. The evaluation results are shown in Table 1.
[0400] <Wiring Deformation>
[0401] Flexible wiring substrates were cut using a slicing machine, and the cross-sections were observed using an optical microscope. Wiring deformation was evaluated based on the following evaluation criteria.
[0402] A: No deformation was found in the signal line and grounding line.
[0403] B: No deformation was found in the signal line, but deformation was found in the ground line.
[0404] C: Deformation was found in one pair of signal lines.
[0405] D: Deformation was found in 2 or 3 pairs of signal lines.
[0406]
[0407] As shown in Table 1, it can be seen that in Examples 1 to 21, the dielectric loss tangent is less than 0.005, and the elastic modulus of the surface at 160°C is less than that of the interior at 160°C, thus suppressing wiring deformation.
[0408] Furthermore, it is known that in Examples 1 to 21, the dielectric loss tangent is less than 0.005, and the elastic modulus of at least one surface at 300°C is less than that of the interior at 300°C, thus suppressing wiring deformation.
[0409] On the other hand, it can be seen that in Comparative Example 1, the elastic modulus of the surface at 160°C is the same as that of the interior at 160°C, thus causing wiring deformation.
[0410] Furthermore, it can be seen that in Comparative Example 1, the elastic modulus of the surface at 300°C is the same as that of the interior at 300°C, thus causing wiring deformation.
[0411] Regarding the laminate of Example 14, it was confirmed that the peel strength between layer B and the copper foil was 7 kN / m and the peel strength between layer C and the copper foil was 0.9 kN / m, indicating sufficient adhesion. On the other hand, in the laminate of Comparative Example 1, the peel strength between the film and the copper foil was 3 kN / m, indicating insufficient adhesion.
Claims
1. A film having a dielectric loss tangent of 0.005 or less, The storage modulus of at least one surface of the membrane at 160°C is less than that of the interior at 160°C. The membrane comprises at least one polymer selected from liquid crystal polymers, fluorinated polymers, polymers having cyclic aliphatic hydrocarbon groups and groups having olefinic unsaturated bonds, polyphenylene ethers, and aromatic polyetherketones. The membrane has a layer A and a layer B disposed on at least one side of the layer A. Both layer A and layer B contain liquid crystal polymers. The energy storage modulus of the surface of layer B at 160°C is less than that of the interior at 160°C.
2. The membrane according to claim 1, wherein, The surface has a loss tangent of 0.03 or higher at 160°C.
3. The membrane according to claim 1 or 2, wherein, The internal energy storage modulus at 160°C is above 0.5 GPa.
4. A film having a dielectric loss tangent of 0.005 or less, The energy storage modulus of at least one surface of the membrane at 300°C is less than that of the interior at 300°C. The membrane comprises at least one polymer selected from liquid crystal polymers, fluorinated polymers, polymers having cyclic aliphatic hydrocarbon groups and groups having olefinic unsaturated bonds, polyphenylene ethers, and aromatic polyetherketones. The membrane has a layer A and a layer B disposed on at least one side of the layer A. Both layer A and layer B contain liquid crystal polymers. The energy storage modulus of the surface of layer B at 300°C is less than that of the interior at 300°C.
5. The membrane according to claim 4, wherein, The surface has a loss tangent of 0.1 or higher at 300°C.
6. The membrane according to claim 4 or 5, wherein, The internal energy storage modulus at 300°C is above 0.1 GPa.
7. The membrane according to claim 1 or 4, wherein the coefficient of linear expansion is -20ppm / K to 50ppm / K.
8. The membrane according to claim 1 or 4, comprising a filler.
9. The membrane according to claim 8, wherein, The number density of the filler inside is greater than that on the surface.
10. The membrane according to claim 1 or 4, wherein, The liquid crystal polymer has structural units represented by any of the formulas (1) to (3). Equation (1) -O-Ar 1 -CO- Formula (2) -CO-Ar 2 -CO- Equation (3) -X-Ar 3 -Y- In equations (1) to (3), Ar 1 Ar represents phenylene, naphthylene, or biphenylene. 2 and Ar 3 Each of these groups independently represents a phenylene, naphthylene, biphenylene, or a group represented by the following formula (4), where X and Y independently represent an oxygen atom or an imino atom, and Ar 1 ~Ar 3 The hydrogen atoms in the form are optionally and independently replaced by halogen atoms, alkyl groups, or aryl groups. Formula (4) -Ar 4 -Z-Ar 5 - In equation (4), Ar 4 and Ar 5 Each can be represented independently as either phenylene or naphthylene, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkylene group.
11. A film having a dielectric loss tangent of 0.010 or less, The storage modulus of at least one surface of the membrane at 160°C is less than that of the interior at 160°C. The membrane comprises at least one polymer selected from liquid crystal polymers, fluorinated polymers, polymers having cyclic aliphatic hydrocarbon groups and groups having olefinic unsaturated bonds, polyphenylene ethers, and aromatic polyetherketones. The membrane has a layer A and a layer B disposed on at least one side of the layer A. Both layer A and layer B contain liquid crystal polymers. The energy storage modulus of the surface of layer B at 160°C is less than that of the interior at 160°C.
12. A film having a dielectric loss tangent of 0.010 or less, The energy storage modulus of at least one surface of the membrane at 300°C is less than that of the interior at 300°C. The membrane comprises at least one polymer selected from liquid crystal polymers, fluorinated polymers, polymers having cyclic aliphatic hydrocarbon groups and groups having olefinic unsaturated bonds, polyphenylene ethers, and aromatic polyetherketones. The membrane has a layer A and a layer B disposed on at least one side of the layer A. Both layer A and layer B contain liquid crystal polymers. The energy storage modulus of the surface of layer B at 300°C is less than that of the interior at 300°C.
13. The membrane according to any one of claims 1, 4, 11 to 12, further comprising layer C, The membrane has, in sequence, layer B, layer A, and layer C.
14. A laminated body having: The membrane according to any one of claims 1, 4, 11 to 12; and A metal layer disposed on the surface of layer A in the membrane.
15. A laminated body having: The membrane according to any one of claims 1, 4, 11 to 12; and A metal layer disposed on the surface of layer B in the membrane.
16. A laminated body having: The membrane according to claim 13; A metal layer disposed on the surface of layer B in the film; and A metal layer disposed on the surface of layer C in the membrane.
17. The laminate according to claim 15, wherein, The metal layer disposed on the surface of layer B is a copper layer disposed on the surface of layer B. The peel strength between layer B and the copper layer is greater than 0.5 kN / m.
18. The laminate according to claim 16, wherein, The metal layer disposed on the surface of layer B is a copper layer disposed on the surface of layer B. The peel strength between layer B and the copper layer is greater than 0.5 kN / m.
19. The laminate according to claim 16, wherein, The metal layer disposed on the side of layer C is a copper layer disposed on the surface of layer C. The peel strength between layer C and the copper layer disposed on the side of layer C is 0.5 kN / m or more.
20. The laminate according to claim 14, wherein, The thickness of layer B is greater than the thickness of the metal layer.
21. The laminate according to claim 15, wherein, The thickness of layer B is greater than the thickness of the metal layer.
22. The laminate according to claim 16, wherein, The thickness of layer B is greater than the thickness of the metal layer.
23. The laminate according to any one of claims 17 to 19, wherein, The thickness of layer B is greater than the thickness of the metal layer.
Citation Information
Patent Citations
Peelable laminated film, peelable laminated film roll, manufacturing method thereof, film, optical film, polarizing plate, manufacturing method of polarizing plate, and liquid crystal display device
JP2013046992A
Liquid crystal polyester film, liquid composition containing liquid crystal polyester and method for manufacturing liquid crystal polyester film
JP2020026474A
Laminate of liquid crystal polyester resin composition and method of preparing the same
CN101531076A
